Persian Walnut (Juglans regia L.) Bud Dormancy Dynamics in Northern Patagonia, Argentina - del Barrio, Ricardo Alfredo; Orioli, Gustavo Adolfo; Brendel, Andrea Soledad; Lindström, Lilia Ivone; Pellegrini, Cecilia Noemí; Campoy, José Antonio (Frontiers in Plant Science, 2022)
Temperate deciduous fruit trees survive winter temperatures by entering a dormant phase in their aerial meristematic organs. Release from bud dormancy occurs after chill requirements (CR) have been satisfied, whereas bud burst/flowering follows heat requirement (HR) fulfilment. The physiological basis behind these metrics remains elusive. Here we are presenting the first multidisiplinary dormancy progression analysis in northern Patagonia, linking 1) forcing/field phenology, 2) bud anatomical development, and 3) soluble sugar (sucrose, glucose and fructose) dynamics in Juglans regia L. CR and HR were determined for ‘Chandler’ and ‘Franquette’, two walnut cultivars with markedly different CR, in artificial chill/forced heat trials (three seasons) and in-field chill/forced heat tests (five seasons) using excised twigs either with or without apical buds (non-decapitated and decapitated). The soluble sugar dynamics of ‘Chandler’ (high-performance liquid chromatography) and the anatomical changes of the buds (light microscopy) of the two cultivars were analyzed during endo-ecodormancy progression in one and two seasons, respectively. The CR defined by artificial chill tests proved to be an overestimation compared to the field determinations. Moreover, the HR were the main driver in the phenology dynamics, as expected for a high-chill region. ‘Chandler’ showed an average of 10.3 field chill portions (CP) and 2,163 Growing Degree Hours (GDH°C) less than ‘Franquette’ for dormancy release and bud burst, respectively. These results were consistent with the transition of the shoot apex from the vegetative to the reproductive phase and the soluble sugar profile. The decrease in sucrose between 15 and 30 days after CR fulfillment could be a reliable biological marker for endodormancy release in walnut, while the increase in fructose and glucose is likely an osmolite and cellulosic carbon source in pre-sprouting. In addition, we discuss the effect of paradormancy thanks to our apical bud experiment (with or without). Our results improve the current understanding of endo-ecodormancy progression in walnut and provide insightful results for walnut production (i.e., cultivation practices such as pruning) as well as for further application in dormancy modelling, to infer the ideotypes that should be bred for future climate conditions.